The Impact of Conferencing Assessment on EFL Students' Grammar Learning - Sasan Baleghizadeh; Zahra Zarghami (Universidad Nacional de Colombia, 2012)
This article reports on a study that was carried out in order to examine the impact of conferencing assessment on students' learning of English grammar. Forty-two Iranian intermediate university students were randomly assigned to an experimental and a control group. The participants in the experimental group took part in four individual and four whole class conferences. The participants in the control group studied the same grammatical points but they were not involved in conferencing assessment. The results of the study showed that the experimental group performed significantly better than the control group on the given post-test. Moreover, the attitudes of the participants toward grammar learning in the experimental group significantly changed from the first administration of a questionnaire to its second administration.